2023
DOI: 10.1167/iovs.64.12.40
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fibroblast Growth Factor Receptor 2 (FGFR2) in Corneal Stromal Thinning

Roy Joseph,
Akosua Boateng,
Om P. Srivastava
et al.

Abstract: Purpose To determine the role of fibroblast growth factor receptor 2 (FGFR2)–mediated signaling in keratocytes during corneal development, a keratocyte-specific FGFR2-knockout (named FGFR2cKO ) mouse model was generated, and its phenotypic characteristics were determined. Methods A FGFR2cKO mouse model was generated by the following method: FGFR2 flox mice were crossed with the inducible keratocyte specific-Cre mice (Kera-rtTA/tet-O-Cre). Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…In addition, the signal transduction of FGFR2b promotes corneal epithelial injury repair, studies have found that FGFR2b knockout mice exhibit reduced proliferation of corneal epithelial cells, as well as loss of lacrimal gland and meibomian gland. FGFR2b is also necessary for the development of submandibular glands ( 119 ). FGF-10 plays a crucial role in the development of the cornea, morphogenesis and growth of the lens and induction and branching of the lacrimal gland and meibomian gland.…”
Section: Growth Factors Involved In Repair Mechanismsmentioning
confidence: 99%
“…In addition, the signal transduction of FGFR2b promotes corneal epithelial injury repair, studies have found that FGFR2b knockout mice exhibit reduced proliferation of corneal epithelial cells, as well as loss of lacrimal gland and meibomian gland. FGFR2b is also necessary for the development of submandibular glands ( 119 ). FGF-10 plays a crucial role in the development of the cornea, morphogenesis and growth of the lens and induction and branching of the lacrimal gland and meibomian gland.…”
Section: Growth Factors Involved In Repair Mechanismsmentioning
confidence: 99%
“…Some spontaneously occurring KC-like murine lines have also been noted [30,31]. Additionally, genetic mouse models based on genes of interest to KC have been attempted [33][34][35][36][37][38][39]71]. However, genetic models may not accurately capture cases of KC influenced by environmental factors or other risk factors.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…In the final and most recent publication, by Joseph et al, a stromal keratocyte-specific Fibroblast Growth Factor Receptor 2 (FGFR2) knockout model was described [39]. This model was based on RNA-seq analyses and immunohistochemistry that identified the downregulation of FGFR2 in both normal and KC human corneal fibroblasts [82,83].…”
Section: Terciero Et Al Described a Prolactin-inducible Protein (Pip)...mentioning
confidence: 99%
See 2 more Smart Citations